Financial Distress and the Role of Management in Micro and Small-Sized Firms - Fernando Alexandre; Sara Cruz; Miguel Portela (Institute of Labor Economics (IZA), 2020)
In this paper, we focus on managerial characteristics of micro and small-sized firms. Using linked employer-employee data on the Portuguese economy for the 2010-2018 period, we estimate the impact of management teams' human capital on the probability of firms becoming financially distressed and on their subsequent recovery. Our estimates show that the relevance of management teams' formal education on the probability of firms becoming financially distressed depends on firms' size and the type of education. We show that management teams' formal education and tenure reduces the probability of micro and small-sized firms becoming financially distressed and increases the probability of their subsequent recovery. The estimates also suggest that those impacts are stronger for micro and small-sized firms. Additionally, our results show that functional experience previously acquired in other firms, namely in foreign-owned and in exporting firms and in the area of finance, may reduce the probability of micro firms becoming financially distressed. On the other hand, previous functional experience in other firms seems to have a strong and highly significant impact on increasing the odds of recovery of financially distressed firms. We conclude that policies that induce an improvement in the managerial human capital of micro and small-sized firms have significant scope to improve their financial condition, reducing the likelihood of firms entering a state of financial distress.
Keywords: G32; J24; L25; 330; financial distress; human capital; firm performance